2008
DOI: 10.1093/pan/mpn018
|View full text |Cite
|
Sign up to set email alerts
|

Fightin' Words: Lexical Feature Selection and Evaluation for Identifying the Content of Political Conflict

Abstract: Entries in the burgeoning “text-as-data” movement are often accompanied by lists or visualizations of how word (or other lexical feature) usage differs across some pair or set of documents. These are intended either to establish some target semantic concept (like the content of partisan frames) to estimate word-specific measures that feed forward into another analysis (like locating parties in ideological space) or both. We discuss a variety of techniques for selecting words that capture partisan, or other, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
269
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(274 citation statements)
references
References 35 publications
2
269
0
3
Order By: Relevance
“…For instance, the pronouns "he" and "she" emerge as highly discriminant words, with Poisson scaling parameter estimates of β = −.54 and β = −1.68 respectively. This is similar to the results of Monroe, Quinn and Colaresi (2008) who found that uncorrected partisan association measures for female pronouns (of the kind that the Poisson scaling model uses) indicated that they were Democrat words. …”
supporting
confidence: 88%
“…For instance, the pronouns "he" and "she" emerge as highly discriminant words, with Poisson scaling parameter estimates of β = −.54 and β = −1.68 respectively. This is similar to the results of Monroe, Quinn and Colaresi (2008) who found that uncorrected partisan association measures for female pronouns (of the kind that the Poisson scaling model uses) indicated that they were Democrat words. …”
supporting
confidence: 88%
“…Politicians may compete over the meaning and hence the political frame of a given issue, indicating that the framing is an important part of politics (Entman 1993). We use the concept of framing in a way similar to that of Monroe et al (2008). Words that are more specific to an individual political party, given the agenda of the speech, will contribute to a higher degree of framing.…”
Section: Strategies Of Mainstream Parties To Handle Challenger Partiesmentioning
confidence: 99%
“…See Table 5 for the ten most important words for each category of this variable using methods developed by [57] and described in detail below.…”
Section: Disappearancementioning
confidence: 99%
“…See Table 6 for the ten most important words for each category of this variable using methods developed by [57] and described in detail below. Freedom of Assembly and Association: This variable measuring freedom of assembly and association is coded 0 when the rights to freedom of assembly or association were severely restricted or denied completely to all citizens; a score of 1 indicates that these rights were limited for all citizens or severely restricted or denied for select groups; and a score of 2 indicates that these rights were virtually unrestricted and freely enjoyed by practically all citizens in a given year.…”
Section: Disappearancementioning
confidence: 99%